Framing Colomina - Tahl Kaminer (Footprint)
Sometime in the 1990s architecture historians shifted their attention from buildings to publications, exhibitions, films and photographs produced by architects. This shift is related to the more general transformation in which ‘society’ has been substituted by ‘culture’. More than any other work it is Beatriz Colomina’s Privacy and Publicity that has come to represent this growing interest of architecture historians. The following review article closely studies the arguments and methodologies at the centre of Privacy and Publicity as a means of delineating the idealism that is the subtext of this shift.